Can investigative audit and whistleblowing systems prevent fraud? - Padri Achyarsyah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to analyze the effect of investigative audits and the implementation of a whistleblowing system on fraud prevention. The data collection method is done by sending a research questionnaire contained in the google form link. The population in this study was 90 auditors at the Deputy for Investigation at the Central Office of the Financial and Development Supervisory Agency (BPKP) of the Special Capital Region of Jakarta. The sampling technique uses saturated samples so that the total sample is 90 auditors. This research method uses descriptive statistics, which are processed with the help of PLS. The study results found that the investigative audit has no significant effect on fraud prevention while implementing the Whistleblowing System significantly impacts fraud prevention. The investigative audit cannot prevent the possibility of abuse early on. This is because investigative audits are conducted after indications of abuse are found or a systematic investigation of evidence is ongoing. Investigative audits conducted by auditors at BPKP DKI Jakarta can now be reactive, meaning that the auditors conduct audits after receiving or obtaining information from other parties regarding the possibility of fraud and fraud crime. Implementing a sound whistleblowing system must also have a whistleblower protection policy. This policy was formed to avoid detrimental actions to the whistleblower so that the whistleblower will feel that his security is maintained.